MUKAYESELİ HUKUKTA İFTİRA, SUÇ İSNADI VE MAHKEME KARARLARI - (:unkn) unknown (My University, 2016)
İftira suçu, Türk Ceza Kanunu'nun (TCK) Millete ve Devlete Karşı Suçlar ve Son Hükümler başlıklı Dördüncü Kısmın, Adliyeye Karşı Suçlar isimli İkinci Bölümünde, 267 nci maddede düzenlenmiştir. Maddenin düzenlenişi ve doktrindeki görüşler değerlendirildiğinde, iftira suçunun mağdurunun tüzel kişi olup olamayacağı hususunda tartışmalar bulunduğu görülmektedir. Nitekim devletin mağdur olup olamayacağı hususu da tartışmalı olup, işbu çalışma kapsamında, bir devletin iftira suçunun mağduru olup olamayacağı, özellikle soykırım suçu çerçevesinde incelenecektir.lerinin soykırım suçunun failleri oldukları iddiasında bulunmak, bir suç isnadı gerçekleşmiş olacağından, şayet 267 nci maddedeki koşullar sağlanıyorsa, iftira suçunun konusunu oluşturabilecektir.Diğer ülkelerin ceza kanunlarına bakıldığında da, iftira suçunun düzenlenişi itibariyle, genel olarak suçun masum kişilere suç isnadında bulunulması şeklinde düzenlendiği görülmektedir. TCK'nın 301 inci maddesinde olduğu gibi, hemen hemen her devletin, ceza kanununda veya çıkarılan bir ek kanunda, kendisine karşı yöneltilen aşağılayıcı, küçük düşürücü veya karalayıcı söylemlere karşı kendini koruduğu ve bu tür ifadelerin kullanılmasını suç olarak düzenlendiği görülmektedir. Bu kapsamda her ne kadar bir devlete karşı yöneltilen soykırım isnatları iftira suçunun konusunu oluşturmaya elverişli bulunmasa da, TCK m.301 gibi diğer ülkelerin kanunlarında da yer alan düzenlemelere, yapılan isnat yöneticilere ilişkin ise, iftira suçunu düzenleyen maddelere başvurulması mümkündür.

Calumny (Slander), is regulated in the Second Chapter ("Crimes Against Justice") of the Fourth Section ("Offences Against the State of the Nation and Final Provisions") of the Turkish Criminal Code. When considering the perpetrator of this crime, there is a debate on the issue of whether legal persons may be the perpetrator of this crime or not. In addition, whether a state may or may not be the perpetrator of this crime, especially on genocide allegations, has been analyzed within this paper. group to another group, (2) A person who commits the offense of genocide is sentenced to heavy imprisonment. (3) The court may adjudicate imposition of security precautions upon the legal entities due to such offenses, (4) These offenses are not subject to statute of limitation." As specified above, the 267th article states that aspersions have to be casted on "persons". Because of the fact that a state cannot be considered as a real person and as the perpetrator of genocide, it is impossible for a state to be the victim of "calumny". However, according to Turkish Criminal Law, as state administrators can be considered as perpetrators of genocide, to make such allegations on these people may give rise to "calumny" if this crime has not been committed. In addition, even if such allegations on a state cannot give rise to calumny according to Turkish Criminal Law, they may be punished according to the 301st article of the Turkish Criminal Code. This article states that "1. Any person who publicly denigrates the Turkish Nation, the Republic and the Grand National Assembly of Turkey, the Turkish Government and State Judicial Organs, shall be sentenced to 6 months to 2 years of imprisonment. 2. Any person who publicly denigrates the military or security organizations shall be sentenced according the first paragraph. 3. Expression of thoughts intended to criticize shall not constitute a crime." This paper shows that, like the Turkish Criminal Code, several countries' criminal codes or other specific codes penalizes these kind of expressions against states. As a result, even if genocide allegations made against a state, are not punishable for calumny under the Turkish Criminal Code, they may be sanctioned based on the 301st article.
Calumny (Slander), Crime Allegation and Court Decisions In Comparative Law
Keywords: Hukuk